Feasibility of a Sheep Welfare Assessment Tool in the Pre-export Phase of Australian Live Export Industry - Collins, Teresa; Anthony, Ursula M. C.; Dunston-Clarke, Emma J.; Fleming, Patricia A. (Frontiers in Animal Science, 2021)
Sheep are exposed to numerous stressors and environments during the pre-export phase of the live export industry. Establishing how animal behavior, health and demeanor reflect their experiences prior to sea transport is the first step toward testing the suitability and practicality of animal welfare measures. A total of 240 merino wethers originating from four farms were assessed at four locations in the live export chain: on farm, upon arrival to the registered export feedlot (Fe1), prior to departing the feedlot (Fe2) and 30 min post loading onto a live export vessel. Each of these locations and time points represent relevant assessment points as part of the commercial live export process. Pen-side behavioral and health measures were collected. Video footage was collected and edited to provide 48 30–45 s duration clips that were then scored by 12 assessors against 10 demeanor terms using a Qualitative Behavioral Assessment (QBA) methodology; data were analyzed using Principal Components (PC) analysis. Repeated Measures ANOVAs tested for variation in each dependent measure across each location and time point. There were low levels of health issues recorded overall; however, seven health and behavior measures significantly varied across the locations and time points. Most vocalizing was recorded on farm; most drinking, eating and resting behaviors were recorded at Fe1 and ruminating at Fe2; while the highest percentage of wethers with ocular discharge and lameness was on the vessel. For QBA, PC1 explained 30.5% of the variability, with agitated and nervous loaded to one end of the axis and calm and relaxed loaded to the opposing end. PC2 explained 24.5% of the variability, with interested, alert and sociable loaded to one end of the axis and lethargic loaded to the opposing end. Spearman's rank correlations between behavior, health and PC scores indicated that wethers eating, ruminating and resting were scored as more calm/relaxed, while those scored as more agitated/nervous or/ lethargic were also likely to vocalize. Determining how wethers respond to the different environments in the immediate pre-export phase of the journey informs on their welfare and the practicality of using a behavior tool to assess animal welfare.